A Traumatic Partial Through-the-Elbow Amputation with Disarticulation of the Humerus: A Case Report and Review of the Literature. Issue 1 (January 2015) - Kanaya, Kohei; Wada, Takuro; Yamashita, Toshihiko
Abstract : Case: A fifty-two-year-old fisherman sustained a severely mangled open elbow dislocation; the distal part of the humerus was protruding from the wound. Although all of the soft tissue attached to the distal part of the humerus was stripped off the bone, no neurovascular structures were damaged. A hinged external fixator was applied and a lateral collateral ligament repair was performed. At the final follow-up, the range of elbow motion was −10° in extension and 125° in flexion, with no instability. Conclusion: Despite the near amputation of the limb, a good functional outcome was achieved because the neurovascular structures remained intact.